Effect of seed size of Berchemia discolor (Klotcsch) Hemsl. on germination and seedling growth - Chakamanga, Munashe Keith Frank (Midlands State University, 2018)
Berchemia discolor is a semi-deciduous tree of Africa that is a valuable for producing timber. A study was conducted to evaluate the influence of seed size on seed germination and seedling quality of Berchemia discolor mature seeds of B. discolor numbering 100 were collected from healthy trees in Buhera, Zimbabwe and the seeds were grouped into three groups in regard to their length, small (<1.5 cm), medium (1.5-2.5 cm) and large (>2.5 cm). The average width and thickness of the B. discolor seeds was calculated as <0.21 g for small seeds, 0.22-0.30 g for medium seeds and >0.31 g for large seeds. The treatments were completely randomized into four replicates. Germination was conducted in germination chambers (incubators) until complete, and the seeds were transplanted into black polythene bags with a mixture of topsoil and cow dug in a ratio of 3:1. Germination percentage was not significantly (P > 0.05) different between the treatments, although large seeds had the highest germination percentage of 94.9%. There were significant (P < 0.05) differences in seedling height and root collar diameter among the different seed sizes, with large seeds having the highest seedlings height and largest root collar diameter. This was attributed to differences in the food reserves. Survival of the transplants from shoot dieback was significantly (P < 0.05) different such that seedlings from large seeds attained the highest survival of 92%. It is therefore recommended that, for production of high quality transplants in the nursery, large sees should be used.